2018
DOI: 10.1002/btm2.10093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical translation of microbe‐based therapies: Current clinical landscape and preclinical outlook

Abstract: Next generation microbe‐based therapeutics, inspired by the success of fecal microbiota transplants, are being actively investigated in clinical trials to displace or eliminate pathogenic microbes to treat various diseases in the gastrointestinal tract, skin, and vagina. Genetically engineered microbes are also being investigated in the clinic as drug producing factories for biologic delivery, which can provide a constant local source of drugs. In either case, microbe‐therapeutics have the opportunity to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 86 publications
0
40
0
Order By: Relevance
“…A greater understanding of gut microbes may lead to different use of medicine in CRC. Gut microbe-based therapeutics are actively used for cancer treatment or prevention ( 39 ). Numerous studies have reported on the use of microbial markers, including microbes and metabolites, to target CRC ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A greater understanding of gut microbes may lead to different use of medicine in CRC. Gut microbe-based therapeutics are actively used for cancer treatment or prevention ( 39 ). Numerous studies have reported on the use of microbial markers, including microbes and metabolites, to target CRC ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only ZPT-containing lipid body wash significantly reduced Staphylococcus abundance at the genus level, and S. aureus at the species level, probably due to the deposition of this active material on skin surfaces and its subsequent interaction with bacterial cells to control their population. Nevertheless, assessment of SCORAD (SCORing of Atopic Dermatitis) scores revealed that AD severity remained unchanged in treated patients [ 68 ], supporting the theory that the impact of microbes in AD results from bacterial communities and their interactions, rather than from isolated bacteria [ 21 , 80 , 81 ].…”
Section: Extrinsic Influences Shaping the Skin Microbiomementioning
confidence: 91%
“…Although metabolic disorders account for only 8% of the indications for microbes, it is worth mentioning this unique niche, as very few cell therapies are investigated for this indication. Microbes exert therapeutic mechanisms of action by (i) displacing pathogenic microbiomes to restore symbiosis and (ii) producing therapeutic biomolecules, a function enabled by genetic modification 33 …”
Section: Clinical Landscapementioning
confidence: 99%
“…Forty‐eight microbe‐based clinical trials were identified (3% of the total trials) (Figure 2) and separated into four main categories based upon consortia‐based/single strain‐based therapy status and indication (Table 8). 4,33,101 Undefined, consortia‐based therapies consist of microbes collected from healthy patient stool banks 101 . The resulting microbe therapeutic ranges from unpurified material stripped only of harmful components (e.g., viruses, pathogens) to material stripped of several species in order to isolate specific microbial phyla with some, or all, individual species remaining unidentified.…”
Section: Current Clinical Trialsmentioning
confidence: 99%